1972
DOI: 10.1172/jci107061
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafiltration of lipoproteins through a synthetic membrane

Abstract: A B S T R A C T To investigate the interaction of lipoproteins with semipermeable membranes, solutions of low density lipoproteins (LDL), very low density lipoproteins (VLDL), mixtures of the two, and diluted, normal, and hyperlipidemic serum were ultrafiltered through a synthetic membrane (500 A nominal pore diameter) using a stirred laboratory ultrafiltration cell. The pressure dependence of ultrafiltrate flux showed that a concentrated layer of lipoproteins was built up at the membrane surface (concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Experimental results indicated that atherogenic lipids may seep into the arterial wall by infiltrating through leaky endothelial cell junctions in regions of high endothelial cell turnover [1 -2]. Previous theoretical and experimental studies [3][4][5][6][7] have revealed that because the endothelium of artery displays low permeability to plasma proteins, the filtration flow across artery wall may cause 'concentration polarization' of lipids, a well-known mass transport phenomenon, at the blood/wall interface with the lipids increasing in concentration from bulk value towards interface [8][9][10][11]. As the blood vessel wall is directly exposed to luminal surface lipid concentration, we have reasoned that it is the concentration of lipids at the blood/vessel wall interface and not the bulk concentration of lipids in blood that has a positive correlation with lipid infiltration into the arterial wall.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results indicated that atherogenic lipids may seep into the arterial wall by infiltrating through leaky endothelial cell junctions in regions of high endothelial cell turnover [1 -2]. Previous theoretical and experimental studies [3][4][5][6][7] have revealed that because the endothelium of artery displays low permeability to plasma proteins, the filtration flow across artery wall may cause 'concentration polarization' of lipids, a well-known mass transport phenomenon, at the blood/wall interface with the lipids increasing in concentration from bulk value towards interface [8][9][10][11]. As the blood vessel wall is directly exposed to luminal surface lipid concentration, we have reasoned that it is the concentration of lipids at the blood/vessel wall interface and not the bulk concentration of lipids in blood that has a positive correlation with lipid infiltration into the arterial wall.…”
Section: Introductionmentioning
confidence: 99%
“…21 Because the endothelium displays low permeability to plasma proteins, the filtration flow across the artery wall causes a concentration polarization at the blood/wall boundary with the macromolecules increasing in concentration from the bulk value towards the interface. 23–25 The driving force for filtration is determined by the transmural hydrostatic pressure and the osmotic pressure difference between the fluid at the luminal surface and the fluid outside the artery wall. When the luminal surface concentration of macromolecules increases, the filtration rate reduces as a result of the enhanced osmotic pressure of the solution in contact with the intimal surface and an additional resistance to filtration flow provided by the condensed macromolecule layer on the luminal surface.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, their accumulation close to the surface of the arterial walls will be strongly influenced by this fluid flow through the tissue [2,3]. Ultrafiltration of the proteins results f r o m their low diffusivities and high solvent d r a g reflection coefficients and may give rise to an unstirred or concentration polarization layer at the blood-waU interface [4,5]. The formation of such a layer would limit fluid flux into the wall either by increasing the local osmotic pressure and therefore reducing the effective driving force or by the formation of a gel layer on the endothelial surface which would reduce its permeability.…”
Section: Introductionmentioning
confidence: 99%